NEW SERVICES OFFERED WITHIN THE REMIT OF TARGET2 – HOW DO THEY CORRESPOND WITH TFEU AND CENTRAL BANK TASKS? (EU and comparative law issues and challenges series (ECLIC), 2019)
When Eurosystem founded TARGET2, its initial purpose was execution of payments. In that sense TARGET2 did not substantially differ from any other Real-Time Gross-Settlement system (RTGS) operated by a central bank. Hence, the service initially offered in TARGET 2 represented (and still represents) a typical central bank task. However, the number of services offered within the remit of TARGET2 increased over time. With the establishment of TARGET2- Securities (T2S) began the Eurosystem’s involvment in enhancing securities settlement. The legal basis for provision of T2S service stated in relevant legal acts remained the same as for the first service (RTGS). The said legal basis is to be found in the TFEU and in the Statute of the ESCB and of the ECB as “promoting the smooth operation of payment systems”. However, the 2015. ruling of CJEU in Case T-496/11 United Kingdom v ECB interpreted the said legal basis narrowly, and it contested the ECB’s competence to make regulations for legal entities engaged in securities clearing. This paper aims to explore if the said ruling could have further repercussions i.e. could it be understood as denying the ECB any competence over securities, including their settlement, which might make Eurosystem’s competence to establish and operate T2S open for discussion. Finally, this paper briefly explains the TIPS service which is also offered within the remit of TARGET2 and whose purpose is execution of payments. Albeit TIPS differs from T2S in that it is clearly a payment service and, as such, can easily be connected with the Eurosystem’s role in promoting smooth operation of payment systems, one must note that the same service is also offered on a commercial basis by private entities. This paper explores how does provision of instant payments correspond with central bank tasks.